Material de referencia piloto: etanol en agua 25 % fracción másica - JULIANA SERNA SAIZ; JOHNNATAN MAURICIO GIRALDO RUALES; IVONNE ALEJANDRA GONZALEZ CARDENAS; LAURA VANESSA MORALES ERAZO; YERALDIN AGUILAR AVILA; Serna Saiz, Juliana; González Cárdenas, Ivonne Alejandra (Instituto Nacional de Metrología - INM, 2020)
Material de referencia piloto: etanol en agua 25 % fracción másica